Timing shapes flyway selection in juvenile white storks at the European migratory divide - Isabel Jorzik; Wolfgang Fiedler; Michael Kaatz; Shay Rotics; Ran Nathan; Martin Wikelski; Andrea Flack (Journal of Ornithology, 2026)
Migratory divides are junctures where populations of the same species following different migratory routes intersect. In white storks ( Ciconia ciconia ), migration strategies differ between the western and eastern flyways, yet the factors influencing flyway selection remain unclear. In this study, we used GPS tracking data from 151 juvenile storks to examine what determines flyway selection of juvenile, first-time migrants. Generalized linear mixed models revealed that timing-related variables were the primary factors correlated to flyway choice. Eastern flyway storks had significantly later fledging dates, shorter pre-migratory periods, and a narrower migration onset window compared to Western flyway storks. While temporal co-occurrence was observed in the overlap areas, western storks generally used these areas earlier. Wind and sex were not found to affect the juvenile flyway choice. Our results show that western storks may be experiencing favorable conditions of reduced time pressure and shorter overall migration routes. These migratory differences could still potentially contribute to the concurrent shift in population dynamics at the migratory divide toward the Western flyway, by inducing carry-over effects or affecting the adults' reproduction success. We suggest that understanding the dynamics of the migratory divide is important for maintaining behavioral diversity and preventing the loss of migratory routes.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Foraging sequence, energy intake and torpor: an individual‐based field study of energy balancing in desert golden spiny mice - Ofir Levy; Tamar Dayan; Shay Rotics; Noga Kronfeld‐Schor (Ecology Letters, 2012)
We studied the relationship between sequence of foraging, energy acquired and use of torpor as an energy‐balancing strategy in diurnally active desert golden spiny mice. We hypothesised that individuals that arrive earlier to forage will get higher returns and consequently spend less time torpid. If that is the case, then early foragers can be viewed as more successful; if the same individuals arrive repeatedly early, they are likely to have higher fitness under conditions of resource limitation. For the first time, we show a relationship between foraging sequence and amount of resources removed, with individuals that arrive later to a foraging patch tending to receive lower energetic returns and to spend more time torpid. Torpor bears not only benefits but also significant costs, so these individuals pay a price both in lower energy intake and in extended periods of torpor, in what may well be a positive feedback loop.